Pengaruh Pengungkapan Corporate Social Responsibility (CSR) Terhadap Kinerja Keuangan Perusahaan (Studi Kasus Perusahaan Manufaktur Sub Sektor Plastik Dan Kemasan Yang Terdaftar Di BEI Tahun 2011-2015) - Syukri (Sekolah Tinggi Ilmu Ekonomi (STIE) Serelo Lahat, 2020)
The research aim is to influence and prove the impact of the disclosure of corporate social responsibility on the financial performance of plastic and packaging manufacturing sub sector companies are listed on the indonesian stock exchange (IDX) in 2011-2015. Company’s financial performance was measured by return on asset and return on equity. The population used in this study were all manufacturing companies plastic and packaging sub sector are listed on the IDX in 2011-2015. The research samples consist of 6 companies by observing 30 and then selected by using purposive sampling. The method of analysis being use in this research was sample linier regression and statistical tests t. The result showed that there are influence variable the disclosure of CSR to financial performance ( was measured by return on asset), known from the P-Value 0,030 ≤ 0,05 and there are no influence variable the disclosure of CSR to financial performance (was measured by return on equity) known from the P-Value 0,287 ≥ 0,05